2011
DOI: 10.1021/la200593p
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress with Functional Biosupramolecular Systems

Abstract: The objective of this account is to summarize our recent progress with functional biosupramolecular systems concisely. The functions covered are artificial photosynthesis, anion transport, and sensing in lipid bilayer membranes. With artificial photosynthesis, the current emphasis is on the construction of ordered and oriented architectures on solid surfaces. Recent examples include the zipper assembly of photosystems with supramolecular n/p-heterojunctions and oriented antiparallel redox gradients. Current tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…Self-assembly of binary composites 2.1 Self-assembling porphyrin-and phthalocyanine-fullerene linked dyads Supramolecular donor-acceptor (D-A) heterojunctions have received considerable attention because of their potential utility for OFETs and OPVs. [17][18][19] Tashiro and Aida et al reported an amphiphilic porphyrin-C 60 linked dyad 1 (Fig. 1), which is self-assembled to form a photoconductive 1D supramolecular D-A heterojunction structure.…”
Section: Tomokazu Umeyamamentioning
confidence: 99%
See 1 more Smart Citation
“…Self-assembly of binary composites 2.1 Self-assembling porphyrin-and phthalocyanine-fullerene linked dyads Supramolecular donor-acceptor (D-A) heterojunctions have received considerable attention because of their potential utility for OFETs and OPVs. [17][18][19] Tashiro and Aida et al reported an amphiphilic porphyrin-C 60 linked dyad 1 (Fig. 1), which is self-assembled to form a photoconductive 1D supramolecular D-A heterojunction structure.…”
Section: Tomokazu Umeyamamentioning
confidence: 99%
“…Provided ideally vertical arrangement of the bicontinuous D-A arrays on the electrodes, such D-A arrays would yield efficient CS and transportation of separated charges to respective electrodes leading to enhanced photocurrent generation. Although nanostructures with bicontinuous D-A arrays have been obtained by self-assembly of D-A molecules on an electrode, 19,62,63,77 it is still difficult to achieve desirable vertical arrangement of bicontinuous D-A arrays on an electrode. 78,79 We developed a novel approach to construct vertical alignment of bicontinuous D-A arrays on a flat SnO 2 electrode for efficient photocurrent generation (Fig.…”
Section: Vertically Self-assembling Porphyrins With Fullerenes On Ele...mentioning
confidence: 99%
“…One of the most promising current bio-photovoltaic without using elaborate or expensive surface chemistries is a PSI complex attached to a semiconductor, achieving a photocurrent density of 362 µA/cm 2 and 0.5 V [15]. Purified complexes [20], photosynthetic membranes [21-24] or whole organisms [25-29] have also been placed on electrodes for assembling biosensors (for review see [30, 31]), mainly for the detection of pollutants, but also as components for future H 2 production devices [32]. As PSI has a higher efficiency and is less prone to photoinhibion than PSII (see later), it could be more suitable for biomimetic devices (for recent reviews see [32-34]).…”
Section: Introductionmentioning
confidence: 99%
“…If incorporated into lipid membranes, these X-shaped bolapolyphiles could provide membrane stabilization or destabilization (channel formation) [71], domain formation [72][73][74][75] and membrane compartmentalization [76] and might contribute to the knowledge about the effects of rod-like molecules (e.g., cholesterol) [75] or superstructures (α-helices of integral proteins) [77,78] on the membrane properties. Furthermore, ordered organizations of π-conjugated systems in lipid membranes are of potential interest for artificial light harvesting systems [79] and transmembrane electronic conduction [80]. In previous work it was shown that the OPE based X-shaped bolapolyphile B12, having two linear dodecyl chains, can form unique hexagonal star shaped domains in the phospholipid model membranes (DPPC, DOPC) of giant unilamellar vesicles (GUVs), obviously stabilizing these vesicles by avoiding faceting at the L α -L β transition [43][44][45].…”
Section: Methodsmentioning
confidence: 99%